A Review of the Effects of Climate Change on Water Resources in Sub-Saharan Africa. - Turyasingura, Benson; Ngabirano, Hannington; Wambui, Kinyi Hellen; Fatima, Sule Mohammed; Ayiga, Natal; Bojago, Elias; Benzougagh, Brahim; Abhishek Banerjee; Kumar, Singh Sudhir (Kabale University, 2024)
Water provides different goods and services like handcraft and fishing materials, water supply for domestic use, businesses, agriculture, transport, washing, drinking, and eco-tourism. However, few studies have assessed the effects of climate change on water resources in recent years. This study investigated the relationship between water resources and climate change in Sub-Saharan Africa. In the first segment, Vos-Viewer was used to map, study the literature, and identify any gaps to evaluate the interdependence between water resources and climate. The study was guided by specific objectives, which include assessing the adaptation and mitigation strategies for the effects of climate on water resources. Searches for the keywords “climate change” and “water resources” were conducted to obtain literature for this study. A total of 125 papers selected for this study from 1945–2022, from Scopus, Google Scholar, Science Direct, and Web of Science, were found relevant for this study and were selected and discussed. Thus, the worldwide literature was used to provide a real understanding of the effects of climate change on water resources, adaptation, and mitigation measures. According to the findings of the study, cooperation networks in developing countries were not as prominent as research networks in developed countries. It was shown that irregular rainfall affects water quality and quantity by giving the water a muddy, acidic, and turbid appearance. Therefore, all stakeholders should facilitate prudent water resource usage by 695 million people who still use unimproved water facilities in sub-Saharan Africa.